ANALYSIS OF SOCIO-CULTURAL INTEGRATION BETWEEN THE BUTON AND IWAN TRIBES IN KOJA DOI VILLAGE - Muhamad, Mahdir (Gema Kampus IISIP YAPIS Biak, 2025)
The aim of this research is to study unique cultural forms, dominant models and forms of integration, as well as factors that encourage and inhibit integration between the Buton and Iwan tribes in Koja Doi Village. Social and cultural integration means that everyone in society works together, whether individuals, families, institutions, or society as a whole. Thus producing unity, which means that everyone agrees on the same values. Qualitative ethnographic research is used to obtain data naturally through observation, in-depth interviews, and documentation. The research results show that the culture of mutual cooperation or what is called "padarane" is a characteristic of the Buton and Iwan tribes, which is manifested in traditional religious ceremonies and social development. One of the dominant models and forms of integration of the Buton and Iwan tribes is community integration on the basis of togetherness in the social development of life. Factors that encourage integration between the Buton tribe and the Iwan tribe are inter-tribal marriages and economic dependence. However, the tribal factors of the two tribes are a barrier to integration.